2019
DOI: 10.1017/brimp.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on the Transition Support Needs of Indigenous Australians Following Traumatic Brain Injury

Abstract: Objective:A growing body of qualitative literature globally describes post-hospital experiences during early recovery from a traumatic brain injury. For Indigenous Australians, however, little published information is available. This study aimed to understand the lived experiences of Indigenous Australians during the 6 months post-discharge, identify the help and supports accessed during transition and understand the gaps in service provision or difficulties experienced.Methods and Procedure:Semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Health care needs may also differ across urban, remote and discrete Aboriginal and Torres Strait Islander communities (Queensland Health, 2010, 2014. Health professionals must recognise and acknowledge these aspects of diversity and tailor their services to ensure culturally secure practice and that the unique values, cultural needs and rights of Aboriginal and Torres Strait Islander peoples are met (Armstrong et al, 2019;Fitts et al, 2019;Hersh et al, 2019;Queensland Health, 2010, 2014Taylor & Guerin, 2014). Failure to do so may lead to patient dis-engagement in the health service, negative emotions and poorer health outcomes for Aboriginal and Torres Strait Islander peoples, particularly those who experience stroke and TBI, and subsequent acquired communication disorders (Armstrong et al, 2019;Fitts et al, 2019;Hersh et al, 2019;Katzenellenbogen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care needs may also differ across urban, remote and discrete Aboriginal and Torres Strait Islander communities (Queensland Health, 2010, 2014. Health professionals must recognise and acknowledge these aspects of diversity and tailor their services to ensure culturally secure practice and that the unique values, cultural needs and rights of Aboriginal and Torres Strait Islander peoples are met (Armstrong et al, 2019;Fitts et al, 2019;Hersh et al, 2019;Queensland Health, 2010, 2014Taylor & Guerin, 2014). Failure to do so may lead to patient dis-engagement in the health service, negative emotions and poorer health outcomes for Aboriginal and Torres Strait Islander peoples, particularly those who experience stroke and TBI, and subsequent acquired communication disorders (Armstrong et al, 2019;Fitts et al, 2019;Hersh et al, 2019;Katzenellenbogen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Aboriginal patients preferred to have access to a familiar interpreter, such as a family member or known health worker (Kelly et al, 2012). Poor intercultural communication may compromise patient's health and health outcomes due to miscommunication and inappropriate information to make informed decisions, particularly those who have experienced stroke or TBI (Armstrong et al, 2019;Fitts et al, 2019;Katzenellenbogen et al, 2013;Queensland Health, 2014). Language and cultural difference between the patient and the health professional, along with culturally insensitive practices, have been identified by Australian Aboriginal and Torres Strait Islander patients as having a negative effect on their well-being and health outcomes (Armstrong et al, 2019;Aspin, Brown, Jowsey, Yen, & Leeder, 2012;Fitts et al, 2019;Hersh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Acquired brain injury, as a result of stroke and traumatic brain injury, affects Australia's First Peoples (hereafter referred to as Aboriginal people) at a significant rate (Esterman et al, 2018, Katzenellenbogen et al, 2018, Katzenellenbogen et al, 2016, You et al, 2015 and the impact is felt by individuals, families and communities (Armstrong et al, 2015(Armstrong et al, , 2019a(Armstrong et al, , 2019b. However, access to brain injury rehabilitation services for Aboriginal people is reported to be often limited, and there is very little support outside of the hospital environment for the person involved, extended family or community (Armstrong et al, 2015, 2019a, 2019b, Fitts et al, 2019. Our recent research involving Aboriginal brain injury survivors and their families revealed that people often manage 'on their own' following such events.…”
Section: Introductionmentioning
confidence: 99%
“…Access to services is reported as problematic for many Aboriginal people, with barriers identified as communication breakdowns, racism and distance from established services in regional and remote contexts [12,13,14,15]. However, with the exception of a small number of studies [12,16,17,18,19,20] most have investigated Aboriginal and non-Aboriginal health professionals' perspectives on the issues involved rather than that of Aboriginal patients themselves. The importance of obtaining the Aboriginal perspective is increasingly acknowledged as part of service focus on client-centred and family-centred care.…”
Section: Introductionmentioning
confidence: 99%